A Bioeconomic Analysis of the East Johore Prawn Fishery - Mohd Noh, Kusairi (Universiti Putra Malaysia Press, 1995)
This study presents the results of the bioeconomic simulations of the east Johore prawn fishery. There are about 17 praml species in east Johore but the model was based on an aggregated prawn fishery harvested by three methods: traditional (consisting of traps and drift nets), small trawlers, and large trawlers. The model was used to simulate several management alternatives (I) limited entry regulation (affecting the number of boats) (2) mesh size regulation (by varying the age at first capture) and (3) combination of these two measures. The base model simulates the actual fishery fairly well and the simulation points to the need to reduce fleet size and increase the age at first capture. The best combination was obtained by a reduction of fleet size by 10% from the current level of about 800 vessels and an increase of age at first capture from the base value of four to six months.